The Gospel according to Dr. Seuss : [snitches, sneeches, and other creachas] - Kemp, James W. (Valley Forge, PA : Judson Press, 2004)
Publisher's description: The stories of one of the world's most beloved children's authors are both imaginative and entertaining. But a closer look at Dr. Seuss's stories reveals that many are inspirational as well as instructive. James Kemp has identified as his favorite theologian not Barth or Pannenberg, but the inimitable Dr. Seuss. In this readily accessible resource, Kemp finds parallels between the actions of cats in hats, Grinches, Snitches, Sneetches, and other Creachas and lessons found in Scripture. Thus, as the author shares his enthusiasm for the creativity and wisdom of Dr. Seuss, both the meaning and the relevance of many Bible passages come to life.
Horton hatches the egg -- Yertle the turtle -- What was I scared of? -- Cat in the hat comes back -- Zax -- How the grinch stole Christmas! -- Horton hears a who! -- Green eggs and ham -- Bartholomew and the oobleck -- Sneetches -- Butter battle book -- Grinch (again) -- On beyond zebra!.
Keywords: Christian life; Seuss, -- Dr